The nature of spin trimer in Ca3Cu2Ni(PO4)4: Магнетизм - Ghosh, M.; Ghoshray, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The nature of spin trimer and 3d spin dynamics in Ca3Cu2Ni(PO4)4 was studied using 31P NMR measurements. This material is obtained replacing one of the Cu ions by a Ni ion in one dimensional spin trimer compound Ca3Cu3(PO4)4. NMR spectrum suggests the presence of two types of magnetically inequivalent phosphorous atoms as in the parent compound. This finding reveals the presence of only one type of trimer viz.Cu2–Ni–Cu2 rather than three types viz., Cu2–Cu1–Cu2, Cu2–Cu1–Ni and Ni–Cu1–Ni as suggested from neutronscattering. Hence the ground state of Ca3Cu2Ni(PO4)4 appears to be a quintet. The present finding also explains the magnetic susceptibility behavior showing no indication of the reduction of net spin of a trimer inCa3Cu2Ni(PO4)4, as expected for JNi–Cu = – 0.85 meV compared to JCu–Cu = – 4.74 meV, reported from neutronscattering. The spin lattice relaxation rate suggests that the three magnon mediated scattering process, dominantin Ca3Cu3(PO4)4, is reduced in Ca3Cu2Ni(PO4)4.